2010
DOI: 10.1002/cpe.1591
|View full text |Cite
|
Sign up to set email alerts
|

Extreme scalability challenges in micro‐finite element simulations of human bone

Abstract: Coupling recent imaging capabilities with microstructural finite element (µFE) analysis offers a powerful tool to determine bone stiffness and strength. It shows high potential to improve individual fracture risk prediction, a tool much needed in the diagnosis and treatment of osteoporosis that is, according to the WHO 1 , second only to cardiovascular disease as a leading health care problem. We adapted a multilevel preconditioned conjugate gradient method to solve the very large voxel models that arise in µF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…16, No. 9, 993-1001, http://dx.doi.org/10.1080/10255842.2011 accounts for bone micro-architecture, and typically requires large computing resources (Bekas et al 2010). Numerous studies have successfully reported accurate estimations of bone mechanical properties with microFE at various skeletal sites, such as the distal radius (MacNeil and Boyd 2008), vertebrae (Wolfram et al 2010), tibia (Rajapakse et al 2010) and proximal femur (Pistoia et al 2001).…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…16, No. 9, 993-1001, http://dx.doi.org/10.1080/10255842.2011 accounts for bone micro-architecture, and typically requires large computing resources (Bekas et al 2010). Numerous studies have successfully reported accurate estimations of bone mechanical properties with microFE at various skeletal sites, such as the distal radius (MacNeil and Boyd 2008), vertebrae (Wolfram et al 2010), tibia (Rajapakse et al 2010) and proximal femur (Pistoia et al 2001).…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…For mFE modeling of nonlinear mechanical behavior (yield, failure, etc.) generally requires parallelized computing on high-performance computing (HPC) clusters [111,112].…”
Section: Biomechanical Analysismentioning
confidence: 99%
“…Furthermore, it has become of increasing interest due to the substantial increment in the number of cores available in emerging architectures (Devine et al, 2006; Zhou et al, 2012). In particular, the use of ParMETIS-based partitioning algorithms for parallel finite-element method simulations has been widely reported in the literature (Piggott et al, 2008; Sahni et al, 2009; Bekas et al, 2010; Shadid et al, 2010; Niederer et al, 2011). In the current section, we also consider an often neglected aspect of the problem: the design of a scalable algorithm that, given a ParMETIS partition, reads the mesh from disk and creates the relevant data structures.…”
Section: Parallelisationmentioning
confidence: 99%